Trade liberalization and green supply chains: impacts on sustainability and energy transition - Yin, Xuan; Sun, Wenchuan; Guo, Qianghua; Zhang, Yanghui; Pang, Ziqi (Transformations In Business & Economics, 2026)
Global economic integration and sustainability challenges underscore the need to examine trade liberalization, green supply chains, and energy transitions. Using a mixed-methods framework, this study addresses the limitations associated with single-method approaches, combining thematic qualitative analysis with quantitative correlation analysis. Data were gathered from 427 participants in Chengdu, encompassing surveys and 30 semi-structured interviews. The mixed-method approach offers a more reliable assessment of policy effectiveness. Notably, this method combines quantitative analysis with real-world market insights. The study results highlight that both trade liberalization and governmental policy measures result in higher adoption of eco-friendly supply chains and energy transition efforts. Hence, the study findings put forward practical guidance to policymakers and industrial stakeholders to develop successful sustainability programs that will help advance sustainable economic growth. Based on this, policymakers must enhance regulatory frameworks and incentives for green technologies, while industries should proactively adopt flexible and sustainable supply chain strategies, in order to support long-term competitiveness and environmental performance.